Zipf's Law and Canadian Urban Growth. (June 2014) - Lalanne, Aurélie
The purpose of this paper is to study the hierarchical structure of the Canadian urban system and to determine the growth processes. Zipf's law is rejected for the whole country for all periods because of a clear size-domination by a few big cities such as Toronto, Montreal and Vancouver. It appears that the dynamics of growth follow a deterministic process related to existing urban size, previous growth and spatial structure. Splitting the Canadian urban system into two—east and west—permits the identification of differences that were not observable when studying the country as a whole. While size and previous growth are still important explanatory variables of growth patterns, these two systems may be distinguished one from the other from the point of view of spatial patterns of distribution of growth rates.